2008
DOI: 10.1007/s10439-008-9477-0
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic Characteristics of In Vitro Vital and Devitalized Rat Aorta and Human Arterial Prostheses

Abstract: The arterial wall viscoelasticity plays an essential role in the vascular responsiveness to vasoactive drugs or pathologies. The aim of this investigation was to derive and compare resonance curve (RC), natural frequency (f(0)), dynamic modulus of elasticity (E'), and coefficient of viscosity (beta) of (i) vital and devitalized preparations of rat thoracic and abdominal aorta, (ii) human arterial prostheses, and to study the histomorphology of vital and devitalized rat aorta. The method of low frequency forced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
5
1
Order By: Relevance
“…Results from more recent studies on the frequency dependency of arterial wall viscosity have not resulted in a convergence in findings. Although some investigators have found that wall viscosity decreases with HR with no change in arterial stiffness, 35 others have found that, at higher frequencies, in the range of HRs tested in this study (300 -450 oscillations per minute), the rat aorta wall may become more susceptible to stiffening, 36 especially at higher pressures. 33 Our finding that the effect of HR on PWV was more evident at higher MAP is consistent with the latter observation.…”
Section: Tan Et Al Heart Rate Dependency Of Aortic Stiffnesscontrasting
confidence: 54%
“…Results from more recent studies on the frequency dependency of arterial wall viscosity have not resulted in a convergence in findings. Although some investigators have found that wall viscosity decreases with HR with no change in arterial stiffness, 35 others have found that, at higher frequencies, in the range of HRs tested in this study (300 -450 oscillations per minute), the rat aorta wall may become more susceptible to stiffening, 36 especially at higher pressures. 33 Our finding that the effect of HR on PWV was more evident at higher MAP is consistent with the latter observation.…”
Section: Tan Et Al Heart Rate Dependency Of Aortic Stiffnesscontrasting
confidence: 54%
“…Large elastic arteries such as the aorta exhibit nonlinear blood pressure-dependent mechanical wall behavior [1][2][3]. The arterial wall exhibits both elastic and viscous properties at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Large elastic arteries such as the aorta exhibit nonlinear blood pressure-dependent mechanical wall behavior [ 1 , 2 , 3 ]. It possesses both elastic and viscous properties at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Such mechanical behavior is referred to as viscoelastic, and its characteristics are often considered as measures of arterial stiffness and compliance. The biomechanical properties of the aorta have been studied extensively over the past few decades using various methods [ 1 , 3 , 4 , 5 ]. Without nervous and humoral regulation by the organism, the direct basal viscoelasticity assessment is performed in vitro using partial or cylindrical arterial segments [ 2 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%